2020
DOI: 10.3390/jof6010029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seedling Age on Colonization Patterns of Citrus limon Plants by Endophytic Beauveria bassiana and Metarhizium anisopliae and Their Influence on Seedlings Growth

Abstract: The inoculation methods, the fungal strains, and several other factors are known to influent the success of fungal entomopathogens colonization in plants. The physiological status of the plant could also be another determinant. In the present study, the ability of three strains of Beauveria bassiana and one strain of Metarhizium anisopliae to successfully colonize Citrus limon plants and the influence of seedling age on endophytic colonization success was examined. Three, 4, and 6 months old seedlings were ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…The main reason for artificial introduction of insect fungal pathogens into plants is for (indirect) control of pest insects. Examples include control of larvae of the European corn borer, Ostrinia nubilalis (Hübner) and Rachiplusia nu , 23,24 the bean stem maggot ( Ophiomyia phaseoli ), 16 aphids ( Aphis fabae , Aphis gossypii , and Acyrthosiphon pisum) , 25 the banana weevil ( Cosmopolites sordidus ), 26 the poppy stem gall wasp ( Chortoicetes terminifera ), 27 the cotton bollworm ( Helicoverpa zea ), 17,28,29 diamondback moth ( Plutella xylostella ) larvae, 30 and the Asian citrus psyllid ( Diaphorina citri ) 20 . However, significant differences in control efficiency has been reported in the earlier mentioned examples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for artificial introduction of insect fungal pathogens into plants is for (indirect) control of pest insects. Examples include control of larvae of the European corn borer, Ostrinia nubilalis (Hübner) and Rachiplusia nu , 23,24 the bean stem maggot ( Ophiomyia phaseoli ), 16 aphids ( Aphis fabae , Aphis gossypii , and Acyrthosiphon pisum) , 25 the banana weevil ( Cosmopolites sordidus ), 26 the poppy stem gall wasp ( Chortoicetes terminifera ), 27 the cotton bollworm ( Helicoverpa zea ), 17,28,29 diamondback moth ( Plutella xylostella ) larvae, 30 and the Asian citrus psyllid ( Diaphorina citri ) 20 . However, significant differences in control efficiency has been reported in the earlier mentioned examples.…”
Section: Introductionmentioning
confidence: 99%
“…Although several insect fungal pathogens have been introduced into different plants as endophytes, plant colonization and effects on host plant growth, resistance against pest insects or microbial pathogens have been reported to vary significantly between different fungal species, the method of inoculation, as well as the physiological status of the plant. 20 For example, both B. bassiana and Metarhizium anisopliae have been shown to endophytically colonize cassava roots following soil drench inoculation, however neither was found in the leaves or stems of the treated cassava plants. Differences in colonization success and plant growth have also been reported among different fungal pathogen treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, growth medium, plant age and species, inoculum density, and fungal species, as well as the rate of conidia application, affect endophytic colonization [ 10 ]. Bamisile et al [ 11 ] reported the influence of seedling age on B. bassiana and M. anisopliae successful colonization in the citrus plant. From their point of entry, microbes may systemically colonize plants from roots to shoots, shoots to flowers or fruits, and/or from flowers to fruits and seeds, and they may also cause localized colonization inside/outside plant organs [ 12 ].…”
Section: Colonization Mechanismmentioning
confidence: 99%
“…A growing number of studies have demonstrated the ability of EPF to promote plant growth when colonized artificially with various inoculation methods (Kabaluk & Ericsson 2007;García et al 2011;Sasan & Bidochka 2012;Liao et al 2014;Lopez & Sword 2015;Jaber & Enkerli 2016;Jaber & Enkerli 2017;Dash et al 2018;Bamisile et al 2020). In a field study, Kabaluk and Ericsson (2007) found an increased yield of corn when seeds were treated with Metarhizium brunneum.…”
Section: Endophytic Insect Pathogenic Fungi As Plant Growth Promotersmentioning
confidence: 99%
“…Other than B. bassiana, several species of Metarhizium also exhibited negative effects against insects from different feeding guilds (Bamisile et al 2020;Canassa et al 2020;Ment et al 2020). For example, endophytic strains of Metarhizium robertsii reduced relative growth rate of black cutworm, Agrotis ipsilon (Hufnagel) (Lepidoptera: Noctuidae) in maize (Ahmad et al 2020); corn stalk borer, Sesamia nonagrioides Lefebre (Lepidoptera: Noctuidae) in sweet sorghum (Mantzoukas et al 2015).…”
Section: Endophytic Insect Pathogenic Fungi As Insect Antagonistsmentioning
confidence: 99%